Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1029/2006jd007708
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of fossil and contemporary carbon sources to PM 2.5 aerosols at nine Interagency Monitoring for Protection of Visual Environments (IMPROVE) network sites

Abstract: Particulate matter aerosols contribute to haze diminishing vistas and scenery at national parks and wilderness areas within the United States. To increase understanding of the sources of carbonaceous aerosols at these settings, the total carbon loading and 14C/C ratio of PM 2.5 aerosols at nine Interagency Monitoring for Protection of Visual Environments (IMPROVE) network sites were measured. Aerosols were collected weekly in the summer and winter at one rural site, two urban sites, five sites located in natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 25 publications
7
76
0
Order By: Relevance
“…tracers for anthropogenic emissions, such as acetylene, but that budgets of organic aerosol production are poorly represented by current understanding based on yields for individual VOCs measured in smog chambers (de Gouw et al, 2005Quinn et al, 2006;Sullivan et al, 2006). The contribution of biogenic VOCs to organic aerosol production remains uncertain, although recent analysis of radiocarbon in organic aerosol has suggested that a large fraction comes from biogenic sources, even in areas with large anthropogenic VOC emissions (Bench et al, 2007;Schichtel et al, 2008;Weber et al, 2007). Because the yield of SOA from the NO 3 +isoprene reaction (Ng et al, 2008) is some 5-8× larger than from photochemical isoprene oxidation (Kroll et al, 2005), its nighttime oxidation is a mechanism by which biogenic VOCs can more efficiently form SOA in polluted air masses.…”
Section: Secondary Organic Aerosolmentioning
confidence: 99%
See 3 more Smart Citations
“…tracers for anthropogenic emissions, such as acetylene, but that budgets of organic aerosol production are poorly represented by current understanding based on yields for individual VOCs measured in smog chambers (de Gouw et al, 2005Quinn et al, 2006;Sullivan et al, 2006). The contribution of biogenic VOCs to organic aerosol production remains uncertain, although recent analysis of radiocarbon in organic aerosol has suggested that a large fraction comes from biogenic sources, even in areas with large anthropogenic VOC emissions (Bench et al, 2007;Schichtel et al, 2008;Weber et al, 2007). Because the yield of SOA from the NO 3 +isoprene reaction (Ng et al, 2008) is some 5-8× larger than from photochemical isoprene oxidation (Kroll et al, 2005), its nighttime oxidation is a mechanism by which biogenic VOCs can more efficiently form SOA in polluted air masses.…”
Section: Secondary Organic Aerosolmentioning
confidence: 99%
“…The reaction is known to produce unsaturated organic nitrates with a yield of approximately 80% as first-generation products (Barnes et al, 1990). These nitrates consist of unsaturated hydroxy-, hydroperoxy-and carbonyl nitrates (Kwok et al, 1996;Skov et al, 1992Skov et al, , 1994Tuazon et al, 1999;Berndt and Boge, 1997), with a recent study also showing evidence for formation of dinitrates and oligomers (Ng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(e.g., Georgia), whereas the maxima sulfate and nitrate occur much further north (e.g., Ohio) based on rural IMPROVE network and urban Speciation Trends Network (STN) surface observations (19). The organic aerosol in the SE U.S. is mostly secondary, with radiocarbon ( 14 C) measurements indicating 70% or more of the carbon is modern (rather than fossil) in rural locations and therefore likely of biogenic origin (35,36).…”
Section: Evidence Of Aerosol Chemical Composition In the Eastern Usmentioning
confidence: 99%